Estudo da capacidade de adsorção do carvão ativado de osso bovino para remoção de ácidos naftênicos em mistura modelo e real de querosene de aviação - Santos, Débora Federici dos (2020)
Aviation kerosene is one of the petroleum derivatives obtained by the distillation of crude oil at temperatures ranging from 150 to 300 oC. The presence of naphthenic acids in this fuel provides thermal instability and increased acidity, which consequently increases the corrosion effect on aircraft engines. Naphthenic acid removal can be obtained by adsorption employing porous materials. Thus, the main objective of this work was to evaluate bovine bone activated charcoal (CAB) for its ability to remove n-dodecanoic acid (AD) in model and real mixture of aviation kerosene through data experimental obtained in kinetics and adsorption isotherm. In the kinetic assay, the equilibrium was reached at 180 min for model mixture and 180 min for real mixture, and the theoretical models that best fits the experimental data were pseudo-first and pseudo- second order, respectively. The results indicated a relatively fast adsorption when compared to the use of other adsorbents presented in literature, such as mesoporous sieves and modified perovskites. In the adsorption isotherm, it was found that the amount adsorbed in the equilibrium in model and real mixture was 600 and 780 mg g -1 , respectively. The model with the best fit was that of Freundlich. It was possible to recover the CAB after the adsorptive process by thermal regeneration. Finally, a comparative study was carried out, regarding the efficiency of AD removal, between the CAB and the polymer filtration system used by the fuel distribution company. CAB was the most efficient and could become a viable, inexpensive and regenerative option for use as a filter material.